Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/ange.201503672
|View full text |Cite
|
Sign up to set email alerts
|

Complete Proton Transfer Cycle in GFP and Its T203V and S205V Mutants

Abstract: Proton transfer is critical in many important biochemical reactions. The unique three-step excited-state proton transfer in avGFP allows observations of protein proton transport in real-time. In this work we exploit femtosecond to microsecond transient IR spectroscopy to record, in D 2 O, the complete proton transfer photocycle of avGFP, and two mutants (T203V and S205V) which modify the structure of the proton wire. Striking differences and similarities are observed among the three mutants yielding novel info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Recent developments in our laboratory have extended ultrafast femtosecond optical delay measurements to nanoseconds and milliseconds by seeding dual-amplifiers with subsequent oscillator seed pulses (60 MHz oscillator corresponding to 14 ns steps) and multiple-probing with a high repetition rate probe (10 kHz probe measures spectra of change every 100 µs following excitation). 1 Having demonstrated the potential of this approach, in chemistry 2,3 and biology, particularly for measuring time-resolved infrared (TRIR) spectra of light-activated protein dynamics, 410 here we extend the technique using a higher repetition rate probe system (100 kHz, probing dynamics every 10 µs), providing an order of magnitude increase in information per experiment, compared to our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in our laboratory have extended ultrafast femtosecond optical delay measurements to nanoseconds and milliseconds by seeding dual-amplifiers with subsequent oscillator seed pulses (60 MHz oscillator corresponding to 14 ns steps) and multiple-probing with a high repetition rate probe (10 kHz probe measures spectra of change every 100 µs following excitation). 1 Having demonstrated the potential of this approach, in chemistry 2,3 and biology, particularly for measuring time-resolved infrared (TRIR) spectra of light-activated protein dynamics, 410 here we extend the technique using a higher repetition rate probe system (100 kHz, probing dynamics every 10 µs), providing an order of magnitude increase in information per experiment, compared to our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Isotopes have traditionally been employed to study reaction mechanisms through primary kinetic isotope effects where the isotopomer is transferred, such as in the light-driven proton transfer in green-fluorescent protein. 29,30 The primary kinetic isotope effect arises from the change in the zero-point energy for the heavier atom, but even larger effects have been reported when tunneling plays a role in the reaction mechanism. 30 In the context of visual photochemistry, early studies suggested a primary kinetic isotope effect associated with chromophore proton or hydrogen transfer, but these models have not been sustained.…”
mentioning
confidence: 99%
“…Among the possible light-induced chemical transformations, cis-trans isomerization is an elementary reaction of fundamental importance in triggering the actions of several photoswitches and bio-photoreceptors. Considering the large structural changes and the fast timescale associated to this photoreaction, transient IR spectroscopy appears as a particularly suited technique to investigate its mechanism and dynamics, and has been extensively applied to study photoinduced isomerization both in photoactive proteins, such as GFP [140][141][142][143][144], PYP [145,146], retinal proteins [12,[147][148][149][150][151], bacteriorhodopsin [152], and in small molecular photoswitches in condensed phase. The literature on the argument is extremely rich, so that we will limit this paragraph to the description of only a few, mostly recent, examples.…”
Section: Cis-trans Isomerization In Molecular Photoswitchesmentioning
confidence: 99%